Ruminant feed resources research - Hanson, Jean (International Livestock Research Institute, 1998)
Poor nutrition because of poor quality feeds and fluctuating feed supply is a major constraint to tropical livestock productivity. The need to supply greater quantities of quality fodder requires development of both new forages and feeding strategies that will enhance the efficiency with which conventional on-farm feed resources are used. Research at ILRI has identified a range of herbaceous forages and fodder tree species which can be used to alleviate the constraints of lack of feed and which can be incorporated as part of sustainable farming systems. Recognising the importance of feed resources research as part of integrated efforts in increasing livestock productivity, ILRI will continue strategic research on the estimation of feed value and use of forages and crop residues and will link this with new research capacity in rumen microbiology and phytochemistry. Ruminant feed resources research at ILRI studies the interactions between feeds and rumen function and includes three projects which cover the forage resources, their linkages with rumen function and their utilisation by the animal. This paper discusses the conservaiton and characterisation of forage genetic resources, rumen microbiology for feed utilisation enhancement, and feed utilisation improvement for enhancing livestock productivity.